PSYCHOLOGICAL REHABILITATION OF RETURN MIGRANTS: PRACTICAL APPROACHES - Ergasheva Mazluma Xusan qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article  explores  the  psychological  rehabilitation  of  return migrants, focusing on practical approaches that facilitate their social and emotional reintegration.  The  study  highlights  common  psychological  challenges  faced  by returnees,  such  as  stress,  cultural  adjustment  difficulties,  and  social  isolation.  It examines effective therapeutic methods, including cognitive-behavioral therapy, group counseling, and community support programs, emphasizing culturally sensitive and holistic  rehabilitation  strategies.  The  article  concludes  with  recommendations  for improving  access  to  mental  health  services  and  strengthening  support  systems  for return migrants.